The Effects of NaCl on Hydrogen Permeation and Sulfide Stress Cracking Resistance of C110 High-strength Steel. Issue 10 (1st October 2022) - Liu, Lianlian; Chen, Lin; Case, Raymundo
Abstract : Sulfide stress cracking (SSC) limits the application of high-strength low-alloy carbon steel C110 in the oil and gas industries. Chloride ions (Cl − ) play an indispensable role in SSC. This study aims to evaluate the effects of NaCl on hydrogen permeation and SSC susceptibility by electrochemical techniques including hydrogen permeation test and electrochemical impedance spectroscopy (EIS), and the novel notched tensile slow strain rate test on carbon steel C110 under wet-H2 S environments. The results show that the higher concentration of Cl − reduces hydrogen absorption and enhances SSC susceptibility. However, it is widely accepted that the reduction in hydrogen absorption results in an increase in SSC resistance. To figure out the role of Cl − in the SSC mechanism, the morphology of the side and the cross-sectional surface were observed. It was found that a higher pit density in a condition with a higher Cl − concentration leads to increased SSC susceptibility as pits act as crack initiation sites. The SSC mechanism transfers from hydrogen embrittlement to pit-induced cracking when the Cl − concentration in the solution increases.